(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals the scientific and philosophical aspects of the stability of society in the positive aspects of the spiritual and moral factors of the National idea to social development. Spiritual and moral factors are based on the fact that at a new stage of the development of our society, a person is the skills necessary for a new life, accompanied by a change in the spiritual worldview. The awareness of the national identity in society, the formation of national feelings-a substantive feature of the National idea: the fact that it is from the conditions of stability is scientifically based.